Major depressive disorder associated with borderline personality disorder. Clinical case - Ciuffardi Montoya, Carmen (2002)
This research work treats about clinical case of a 25-year-old woman that arrives to consultation because she was experiencing extremely sadness. At the beginning of therapy, the patient had 4 months of pregnancy. In this article we will see the evolution of the patient’ s symptoms, sustained by the psychoanalytical theory, biographical data, personal history, evaluation and integral report, diagnosis, and viable therapeutic plan.